High-frequency induction sintering of B4C ceramics and its mechanical properties. Issue 16 (December 2016) - Shon, In-Jin
Abstract: The nanopowders of B4 Cwere fabricated by high energy ball milling. The nanostructured B4 C powders milled for various time of 0, 1, 4, and 10 h were consolidated within two min using the high-frequency induction heating. The effect of ball milling on sintering, microstructure and mechanical properties (hardness and fracture toughness) of the B4 Cwere investigated using FE-SEM and Vickers hardness tester.